Pola Morfologi dan Perkembangan Kecamatan Natar - Defary, Faishal; Putri, Marsista Buana (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
The development of a city takes place rapidly due to its attractiveness from both economic and non-economic sides. Rural conditions that are inversely proportional to urban areas drive urbanization. Natar District, part of the Bandar Lampung Metropolitan Area and adjacent to Bandar Lampung City, has undergone changes in morphological patterns. Identifying the morphology of a city area is critical for its development to avoid morphological defects or urban sprawl. This research used a deductive approach, referring to Smailes’ theory, identifying morphology using 3 components: road network patterns, land use and building patterns and densities. In 2012, the morphological pattern in Natar District was linear beaded with the Lintas Sumatra Road as a linear line and Radin Inten II Airport Area, Rejosari Station, Natar Traditional Market, and Hajimena Village as beads (morphological core). In 2022, the morphological pattern in Natar District has developed, still having beaded linear pattern, but there are an additional 2 beads as the core morphology, namely the office, trade and services areas Merak Batin and Natar Toll Exit Area. The development of Natar District is influenced by external factors such as its position adjacent to Bandar Lampung City and internal factors such as facilities and infrastructure.